2008
DOI: 10.1021/pr8005777
|View full text |Cite
|
Sign up to set email alerts
|

MALDI Imaging Combined with Hierarchical Clustering as a New Tool for the Interpretation of Complex Human Cancers

Abstract: Proteomics analyses have been exploited for the discovery of novel biomarkers for the early recognition and prognostic stratification of cancer patients. These analyses have now been extended to whole tissue sections by using a new tool, that is, MALDI imaging. This allows the spatial resolution of protein and peptides and their allocation to histoanatomical structures. Each MALDI imaging data set contains a large number of proteins and peptides, and their analysis can be quite tedious. We report here a new ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
239
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(241 citation statements)
references
References 19 publications
1
239
0
Order By: Relevance
“…MSI has several key characteristics that make it well suited to this task; it is an untargeted analysis that can simultaneously analyze hundreds of molecular ions, it can be directly applied to tissue sections, it is inexpensive, and it is fast. Several previous studies have reported MSI's ability to uncover tumor subpopulations in histologically identical regions of tumor tissue (5,20,21). Here we have used dimensionality reduction based on t-SNE followed by bisecting k-means clustering to automatically segment the tumor-specific MSI data from a patient series into an optimum number of subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSI has several key characteristics that make it well suited to this task; it is an untargeted analysis that can simultaneously analyze hundreds of molecular ions, it can be directly applied to tissue sections, it is inexpensive, and it is fast. Several previous studies have reported MSI's ability to uncover tumor subpopulations in histologically identical regions of tumor tissue (5,20,21). Here we have used dimensionality reduction based on t-SNE followed by bisecting k-means clustering to automatically segment the tumor-specific MSI data from a patient series into an optimum number of subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Deininger et al (5) were the first to report that MSI may reveal the biomolecular intratumor heterogeneity associated with a tumor's clonal development. A hierarchical cluster analysis of the MSI data revealed a patchwork of molecularly distinct regions, which were postulated to reflect the tumor's clonal evolution.…”
mentioning
confidence: 99%
“…This molecular information was then combined with clinical data taken from patients in order to predict the survival rate of patients based upon the number of observed molecular tumour sub-populations. This is a prime example of not only how MALDI-MSI can provide information that is confirmatory, or complimentary to histological information, but also how it can provide further information that was not previously possible [15,16].…”
Section: Maldi-msimentioning
confidence: 96%
“…Lots of studies on gastric cancer have been reported recently (Deininger et al, 2008;Li et al, 2008;Khoder et al, 2009;Zhang et al, 2010), and the results showed some clinical significance in the diagnosis of gastric cancer. Lu et al (2010) compared the difference of proteomic analysis between gastric cancer (n = 34) and normal control (n = 30) and found five different protein peaks, by which a diagnostic model was developed and showed a sensitivity of 94.3% and a specificity of 93.3% in the diagnosis of gastric cancer.…”
Section: Gastric Cancer-associated Protein Peaks In Serum Proteomics mentioning
confidence: 97%